A Strategic Analysis of Wal-Mart's Failure in Germany - THAKOR, H (2009)
This research argues that despite increase in international activity by retailers across the globe, and increase in retail internationalization failures, the study on analysis of these failures is sufficiently less. The report acknowledges the fact that the internationalization of firm needs to be accessed from different strategic concepts. These concepts, either external or internal to the firms are important to be studied and analyzed before entering international markets. The report reviews the literature on Porter five forces, Resource-Based View of the Firm, Acquisition as an entry mode strategy, and CAGE framework. Thus, taking a holistic view of different strategic concepts, and referring to past studies and company records, the concepts are then applied to investigate Wal-Mart’s failure in Germany. The analysis helps to understand the effects of various strategic concepts that influenced Wal-Mart’s failure in Germany. The report recognizes the importance of organizational fit between external and internal environment, entry mode strategies and CAGE framework in the overall Retail Internationalization Process. At the end, the report concludes with the difficulties and limitations observed, thereby recommending suggestions for future research.